Determinants of time to first birth among women of childbearing age in Somalia – a survival analysis model - Alin, Abdirahman Osman; Hassan Muse, Abdisalam (European Journal of Clinical and Experimental Medicine, 2025)
Introduction and aim. The study evaluated factors and the significant indicators of time to first birth for reproductive aged women (aged 15–49 years) in Somalia. Material and methods. The study considered SDHS, 2020. The log-rank test was used to assess the statistical significance of the observed difference between waiting time for first birth and various socioeconomic and demographic factors. The Cox proportional hazard model was applied to identify the influential factors for the waiting time to the first birth. Results. The study established that about 71.19% of the respondents got married before the age of 20, while 28.81% did marry after the 20 years of age. Survival analysis revealed that the place of residence, region, age at first marriage, respondent’s education, employment status, and Wealth quintile were statistically significant determinants of waiting time to first birth. The majority of the respondents (64.56%) of the total had their first birth between the ages of 15 and 24. Among these age groups, the highest number of first births occurs at the age of 19 years, with 11.98% of respondents falling into this category. The study also found that the different age groups revealed significantly lower hazards for first births as the age increased. Regarding regional differences, the study found significant variations in the probability of survival of the first birth. In particular, the Togdheer region exhibited a higher hazard ratio (HR=1.132979, p=0.030), indicating an increased risk of experiencing the first birth compared to the reference category. Other regions, such as Galgaduud (HR=1.140067, p=0.029) and Bay (HR=1.199272, p=0.018), also showed higher hazards. On the contrary, Woqooyi Galbeed did not show significant difference in survival probabilities (HR=0.972095, p=0.604) compared to the reference category. Conclusion. Raising the minimum age for the first childbirth and promoting women’s education are crucial for reducing child marriage rates in Somalia.